End‐of‐Life Medical Costs of Medicaid Cancer Patients. (25th November 2014) - Tangka, Florence K.L.; Subramanian, Sujha; Sabatino, Susan A.; Howard, David H.; Haber, Susan; Hoover, Sonja; Richardson, Lisa C.
<x xml:space="preserve">Abstract</x> Objectives To quantify end‐of‐life (EOL) medical costs for adult Medicaid beneficiaries diagnosed with cancer. Data Sources We linked Medicaid administrative data with 2000–2003 cancer registry data to identify 3, 512 adult Medicaid beneficiaries who died after a cancer diagnosis and matched them to a cohort of beneficiaries without cancer who died during the same period. Study Design We used multivariable regression analysis to estimate incremental per‐person EOL cost after controlling for beneficiaries' age, race/ethnicity, sex, cancer site, and state of residence. Principal Findings End‐of‐life costs during the final 4 months of life were about $10, 000 higher for Medicaid cancer patients than for those without cancer. Medicaid cancer patients are more intensive users of inpatient and ambulatory services than are Medicaid patients without cancer. Medicaid cancer patients who die soon after diagnosis have higher costs of care and use inpatient services more intensely than do Medicaid patients without cancer. Conclusions Medicaid cancer patients incur substantially higher EOL costs than noncancer patients. This increased cost may reflect the cost of palliative care. Future studies should assess the types and timing of services provided to Medicaid cancer patients at the EOL.